Mechanistic Insights into Hypoxic Hypoxia: Molecular Responses to Reduced Oxygen Tension, Systemic Compensation, and Pathological Outcomes in Human Physiology - Vladimirovna, Sarkisova Victoria; Faxriddinovna, Gadayeva Zarina; Vitalyevich, Kan Vladimir; Eldarovna, Sarkisova Elmira (American Journal of Biology and Natural Sciences, 2025)
This article provides a comprehensive analysis of hypoxic hypoxia, focusing on molecular mechanisms activated during reduced oxygen tension, systemic compensatory responses, and the subsequent pathological outcomes observed in human physiology. The review integrates current scientific findings on hypoxia-inducible factors, cellular metabolic shifts, cardiovascular and respiratory adaptations, and organ-specific injuries. The article aims to present a clear, structured understanding of how hypoxic hypoxia develops, progresses, and impacts human health. This comprehensive review examines the physiological and cellular adaptations elicited by hypoxic hypoxia, emphasizing molecular signaling pathways, compensatory systemic responses, and the resultant organ-specific pathologies. The manuscript synthesizes findings from experimental research and clinical investigations to elucidate mechanisms governing oxygen sensing, energy metabolism modulation, and tissue preservation under low oxygen conditions. Emphasis is placed on the regulatory roles of hypoxia-inducible factors, mitochondrial adjustments, oxidative stress dynamics, and cardiovascular-respiratory adaptations. By integrating molecular insights with clinical outcomes, the article highlights potential therapeutic targets for mitigating hypoxia-associated morbidity. The study aims to enhance understanding of the intricate balance between protective adaptations and detrimental consequences arising from sustained oxygen deprivation.